Pengaruh Citra Bank, Produk Kredit Dan Tingkat Suku Bunga Terhadap Keputusan Mengambil Kredit Pada PT BPR Indra Candra Singaraja - Ni Nyoman Juli Nuryani; Ni Luh Putu Krispiani (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The results of the study showed that there was an influence of bank image on the decision to take credit at PT BPR Indra Candra of 0.236. The results of the hypothesis test using the t-test showed that the t-count (3.622) was greater than the t-table (1.660). These results indicate that bank image greatly influences customer decisions to take loans at PT BPR Indra Candra. Based on the results of the study, the influence of credit products on the decision to take loans at PT BPR Indra Candra was 0.332. The results of the hypothesis test using the t-test showed that the t-count (3.544) was greater than the t-table (1.660). Therefore, it can be concluded that credit products offered to customers can increase customer desire to apply for loans. The results of the study showed that the influence of interest rates on credit decisions at PT BPR Indra Candra was indicated by a regression value of 0.360. The influence of interest rates on credit decision-making is also supported by the results of hypothesis testing, with the t-test showing that t count > t table (4.128 > 1.660). Based on the results of the study, it can be concluded that interest rates have a strong and positive influence on customer decisions to take out loans. This is evidenced by the existence of competitive interest rates that can influence customers in considering applying for loans to banks.